2020
DOI: 10.1089/photob.2019.4723
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Observational Study and Analysis of Two Different Photobiomodulation Therapy Protocols Combined with Rehabilitation Therapy as Therapeutic Interventions for Canine Degenerative Myelopathy

Abstract: Objective: The objective of this retrospective review was to examine the impact that adding photobiomodulation therapy (PBMt) to rehabilitation therapy had on the pathology of degenerative myelopathy (DM) in canine patients. Background: Canine DM is a progressive, fatal neurodegenerative disease for which there exists a dearth of effective treatments, limiting clinicians to pursue symptom palliation. Methods: Clinical records of dogs referred for presumed DM to a specialty rehabilitation facility were screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…44 PBMT has a documented anti-inflammatory effect, attributed to an improvement in circulation, 45,46 while also aiding in slowing degenerative myelopathy progression. 47 This anti-inflammatory effect may be responsible for the part of the effect we observed in PBMT. The same effect may also be why lower values were recorded in both thermographic views of joints in the PBMT during the treatment period and was still recorded at the +30-day evaluation.…”
Section: Discussionmentioning
confidence: 78%
“…44 PBMT has a documented anti-inflammatory effect, attributed to an improvement in circulation, 45,46 while also aiding in slowing degenerative myelopathy progression. 47 This anti-inflammatory effect may be responsible for the part of the effect we observed in PBMT. The same effect may also be why lower values were recorded in both thermographic views of joints in the PBMT during the treatment period and was still recorded at the +30-day evaluation.…”
Section: Discussionmentioning
confidence: 78%
“…Laser therapy for spinal cord diseases in dogs has limited evidence, as it is uncertain if enough light reaches and is absorbed by neural cells of the spinal cord. In comparison, cadaver studies in mice and rats verified an effect 28–30 . Supplementary to regular physical rehabilitation, perseverance and support of the pet owner are essential parts of the management, as returning to normal neurological function can take a long time.…”
Section: Discussionmentioning
confidence: 88%
“…In comparison, cadaver studies in mice and rats verified an effect. [28][29][30] Supplementary to regular physical rehabilitation, perseverance and support of the pet owner are essential parts of the management, as returning to normal neurological function can take a long time. This dog was ambulatory 3 weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported by studies in rats 48,49 and in humans 50,51 that another mechanism of action of PBMT is to reduce oxidative stress and skeletal muscle fatigue with doses similar to those delivering anti‐inflammatory effects 43,47 . Different studies in veterinary medicine also confirmed these mechanisms of actions and effects, 16,20,52–55 and the most recognised explanation for these is based on the fact that cytochrome c absorbs light from 500 to 1100 nm due to specific properties of this large molecule. Therefore, when under PBMT, the cytochrome will be excited and break bonds with nitric oxide, allowing an easier bond with oxygen and thus leading to the production of cytochrome c oxidase.…”
Section: Discussionmentioning
confidence: 89%